Towards a conceptual model of the impact zone ecology in rivers - Roche, Nicola (Cranfield University, 2014)
In many regions of the world, untreated wastewater is discharged directly into rivers containing sanitary determinands including ammonia, nitrite and organic matter which places a demand on dissolved oxygen in the water. The wastewater may also contain chemical ingredients of home and personal care products. When sewage treatment is lacking, often in developing regions, these sanitary determinands and down-the-drain chemicals may be present at high concentrations in surface waters which may adversely impact the ecological communities present downstream of the effluent outfall. Some studies have studied these ecological effects by sampling the taxa present at regular intervals downstream of an wastewater outfall, from which a common pattern in terms of macroinvertebrate species richness, dominance and diversity throughout the impact zone is evident. The aim of the project was to develop a conceptual model in order to predict the ecological composition downstream of an effluent outfall, as a result of multiple stressors’ concentration gradients. The model combines water quality data and toxicity data of the stressors on aquatic organisms, in the form of species sensitivity distributions (SSDs) to predict this impact. The model was based on selected stressors: ammonia, nitrite and dissolved oxygen which are present, in particular, in untreated wastewater; and two chemical ingredients used in home and personal care products which are washed down-the-drain. The model was applied to data from a field study on the South Elkhorn Creek in Kentucky, USA. Predicted effects on taxonomic composition were in line with field observations, although further enhancements to the model could incorporate more environmental realism. This was a useful step in the direction to creating a conceptual model of the impact zone ecology in rivers.
Keywords: Species sensitivity distributions (SSDs); predictive modelling; untreated wastewater; species richness; traits